Rediscovering Bacon's hydrazine/phenylhydrazine mediated cyclization of 2,2 `-dicarbonylbi(hetero)aryls: construction of (5-azo)-/indazolo[2,3-a]quinolines - Dhote, Pawan S.; Ramana, V. Chepuri (Organic & Biomolecular Chemistry, 2022)
Hydrazine/phenylhydrazine-mediated reductive dicarbonyl coupling reactions have been carried out under mild conditions to provide polycyclic aromatic compounds and azo-substituted polyaromatic compounds. This method has a broad substrate scope with good functional group compatibility.